EXTENSION OF EMPLOYEE CONTRACTS BASED ON PERFORMANCE APPRAISAL AT BNN LAMPUNG PROVINCE USING THE VIKOR METHOD - Cahyani, Cindy Naulina; Handayani, Rani Irma; Normah, Normah (LPPM Universitas Nusa Mandiri, 2021)
The process of an employee contract extension at BNNP Lampung was previously carried out when the contract employee had completed his work contract for one year and during the work process. This results in good work progress and is still needed by the Lampung BNNP, so a report will be made on which employees will be extended their work contract after which the report is given to the Head of the Lampung BNNP to approve the employee contract extension decision letter, for that an appropriate decision support system is needed and efficient so that it can assist in making decisions on employee contract extensions. This decision support system is made based on performance appraisal by predetermined criteria, namely attitude, workability, attendance, a period of employment, and age, if all these criteria are met, the work contract will be extended. This decision support system is created using the Vikor method to obtain the best ranking results taken from alternatives on each criterion that is close to the ideal solution. To produce the best solution in the decision support system for employee contract extension based on the performance appraisal at BNN Lampung Province. The calculation of the Vikor method in this study produces the smallest Q value as the first rank with a value of 0.025 in alternative 6 and the largest Q value as the last rank with a value of 0.8333 in alternative 8.